The Role of the Teacher in Madrasah Ibtidaiyah to Manage Class Towards Child-Friendly - Pamuji, Zuri (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2022)
Teacher is the central figure to manage the class towards a child friendly. The management of child-friendly classes in this case is all effort of the teacher in creating and maintaining optimal conditions for the learning process to occur while still paying attention to the protection of the growth and development of the student’s potential from acts of violence and discrimination so as to achieve the expected learning objectives. In this regard, child-friendly classroom management patterns related to the role of teachers need to be continuously developed, because they are very strategic in supporting the development of the potential of students. This study aims to map the role of the teacher conceptually related to classroom management towards being child-friendly, sourced from various appropriate literature sources. The research results can be described as follows: first, teachers need to manage students which include enforcing rules in class, providing age-appropriate guidance for students, controlling the course of the learning process. Second, the teacher needs to manage the physical classroom, which includes arranging the seating position of the teacher and students as well as the classroom furniture. Meanwhile, the success of MI teachers in managing classes to become child-friendly classes cannot be separated from the support of all stakeholders in the school